Exploring the human lacrimal gland using organoids and single-cell sequencing - Bannier-Hélaouët, Marie; Post, Yorick; Korving, Jeroen; Trani Bustos, Marc; Gehart, Helmuth; Begthel, Harry; Bar-Ephraim, Yotam E.; van der Vaart, Jelte; Kalmann, Rachel; Imhoff, Saskia M.; Clevers, Hans (Cell stem cell, 2021)
The lacrimal gland is essential for lubrication and protection of the eye. Disruption of lacrimal fluid production, composition, or release results in dry eye, causing discomfort and damage to the ocular surface. Here, we describe the establishment of long-term 3D organoid culture conditions for mouse and human lacrimal gland. Organoids can be expanded over multiple months and recapitulate morphological and transcriptional features of lacrimal ducts. CRISPR-Cas9-mediated genome editing reveals the master regulator for eye development Pax6 to be required for differentiation of adult lacrimal gland cells. We address cellular heterogeneity of the lacrimal gland by providing a single-cell atlas of human lacrimal gland tissue and organoids. Finally, human lacrimal gland organoids phenocopy the process of tear secretion in response to neurotransmitters and can engraft and produce mature tear products upon orthotopic transplantation in mouse. Together, this study provides an experimental platform to study the (patho-)physiology of the lacrimal gland. [Display omitted] •Derivation of adult stem cell-based organoids from mouse and human lacrimal gland•Pax6 is essential to maintain lacrimal gland duct identity in adult cells•Single-cell transcriptome analysis of major human lacrimal gland cell types•Lacrimal gland organoids can be induced to cry and are transplantable Lacrimal gland biology remains poorly understood. Here, we establish organoids from mouse and human lacrimal gland that can serve as study subjects for the lacrimal gland in vitro. In addition, we describe the human lacrimal gland at the single-cell level, which provides a platform for future studies.